Cultural heritage and traditional medicine: A cartography of healing practices - Lena N. Canet (Journal of Rural Tourism, 2025)
Purpose - This research explores the intersection of cultural heritage and traditional medicine in the Philippines, emphasizing the importance of preserving indigenous healing practices such as Hilot and herbal medicine amid ongoing modernization and the expansion of formal healthcare systems.Methodology/Design/Approach - A mixed-methods approach was employed, combining qualitative interviews with traditional healers and community members, along with quantitative surveys to assess public perception and usage of traditional medicine.Findings - The study reveals that traditional healing practices remain deeply embedded in Filipino communities and are valued for their therapeutic efficacy. However, these practices face increasing threats from shifting societal attitudes and the economic pressures posed by modern healthcare systems. Originality/Value - This research contributes to the discourse on healthcare pluralism by highlighting the cultural and medical value of indigenous healing traditions. It underscores the need for inclusive health policies that integrate traditional knowledge into contemporary medical frameworks, supporting both cultural preservation and public health.